2013
DOI: 10.3109/00016489.2012.746471
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the BAST-24 smell and taste test in the study of diabetic patients: a new approach to the determination of renal function

Abstract: There was no significant relationship between HbA1c and olfactory and taste sensations. There was a significant relationship between the percentage of correct responses and albuminuria (p = 0.03) and between identification of odours through the olfactory nerve and GFR (p = 0.029), and the percentage of correct responses and GFR (p = 0.03). There was no significant relationship between taste and renal failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 9 publications
3
35
0
Order By: Relevance
“…Although there was [42]. Although Duda-Sobczak et al [41] found no significant difference between olfactory scores in participants with Type 1 diabetes and control participants, further analysis of data comparing odour identification scores between groups with and without diagnosed microvascular complications showed lower scores in participants with neuropathy and retinopathy.…”
Section: Olfactory Dysfunction and Diabetes Complicationsmentioning
confidence: 96%
See 3 more Smart Citations
“…Although there was [42]. Although Duda-Sobczak et al [41] found no significant difference between olfactory scores in participants with Type 1 diabetes and control participants, further analysis of data comparing odour identification scores between groups with and without diagnosed microvascular complications showed lower scores in participants with neuropathy and retinopathy.…”
Section: Olfactory Dysfunction and Diabetes Complicationsmentioning
confidence: 96%
“…Most studies have shown that participants with diabetes complications exhibited more olfactory dysfunction than those without complications [14,16,19,42].…”
Section: Olfactory Dysfunction and Diabetes Complicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…This pilot study comprised of 100 Europid Caucasoid patients with T1D, as defined by the National Diabetes Data Group, and 25 patients of them were considered as Diabetic Control (DC) for the complication study [62][63][64][65][66][67] (Table 1 . Patients with overt DNe were identified by the presence of ankle jerk loss, sensations of pain, foot ulcer, and/or autonomic neuropathy.…”
Section: Methodsmentioning
confidence: 99%